Characteristics of lightweight aggregate produced from lime-treated sewage sludge and palm oil fuel ash - Lau, P.C.; Teo, Delsye Ching Lee; Mannan, Mohammad Abdul (Elsevier Ltd., 2017)
This study investigated the characteristics of lightweight aggregate made from solid waste such as lime-treated sewage sludge, palm oil fuel ash and sodium silicate. These aggregates are produced via sintering at three temperatures of 1160, 1180 and 1200 °C. The properties of sintered pellets namely bulk density, particle density, water absorption, shrinkage index and crushing strength are determined. The properties of the aggregates changed with the addition of binder and firing conditions. The increase of binder content and sintering temperature increased the strength and particle density, and also decreased the water absorption due to the formation of a dense structure. © 2017 Elsevier Ltd